2019
DOI: 10.17475/kastorman.662465
|View full text |Cite
|
Sign up to set email alerts
|

Inocybe mytiliodora: A New Record for Turkey

Abstract: Aim of the study: The aim of the present study is to identify, characterize and record a new agaric for the first time from Turkey. Study area: It covers a total area of approximately 20 ha and is located in Ankara within the boundaries of Çankaya district. Material and method: Basidiomata were collected from Ankara University Tandoğan Campus on September 1, 2018. Macro-and micromorphological properties of basidiomata and nuclear ribosomal large subunit (nrLSU) sequences were used for identification. The vouch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This includes a noteworthy collection of 28 mosses species (Ezer et al, 2021), highlighting the richness of non-vascular plant life in the area. In addition, the campus is home to an extraordinary variety of 174 fungal species (Akata et al, 2019a;2019b;2020;2021a;2021b;Altuntaş et al, 2019;Sahin and Akata 2019;2021). These include 64 microfungi and 24 lichenized fungi, demonstrating the extensive range of symbiotic relationships present within the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes a noteworthy collection of 28 mosses species (Ezer et al, 2021), highlighting the richness of non-vascular plant life in the area. In addition, the campus is home to an extraordinary variety of 174 fungal species (Akata et al, 2019a;2019b;2020;2021a;2021b;Altuntaş et al, 2019;Sahin and Akata 2019;2021). These include 64 microfungi and 24 lichenized fungi, demonstrating the extensive range of symbiotic relationships present within the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Inocybe, belonging to the Inocybaceae family, is an ectomycorrhizal genus that boasts a broad geographical distribution, with species ranging from tropical to arctic regions and they are predominantly encountered in varied forest ecosystems, including both deciduous and coniferous forests (Altuntaş et al, 2019). In terms of physical appearance, Inocybe species are characterized by their relatively small and inconspicuously colored basidiomata (Kuyper, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Marasmius genus contains about 500 species in the family Marasmiaceae (Agaricales, Agaricomycetes, Basidiomycota) and according to presented checklists and the recent studies in Turkey, 12 species have so far been identified belonging to this genus (Kirk et al, 2008;Sesli and Denchev, 2014;Solak et al, 2015;Uzun et al, Akçay et al, 2018;Bozok et al, 2018;Keleş, 2018a;Keleş, 2018b;Sadullahoğlu and Demirel, 2018;Sesli et al, 2018a;Sesli et al, 2018b;Uzun and Kaya, 2018;Altuntaş et al, 2019;Akçay, 2019;Çağlı et al, 2019;Sesli and Bandini, 2019;Acar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%